A Bi-layer TiO2 photoanode for highly durable, flexible dye-sensitized solar cells. Issue 8 (27th January 2015) - Lin, Jianjian; Peng, Yong; Pascoe, Alexander R.; Huang, Fuzhi; Cheng, Yi-Bing; Heo, Yoon-Uk; Nattestad, Andrew; Seung, Wanchul; Kim, Sung Kyun; Yoon, Hoon Joon; Kim, Sang-Woo; Yamauchi, Yusuke; et al.
Abstract : A new photoanode architecture for cold isostatic pressing (CIP), with microstructured TiO2 sea-urchin-like assemblies, composed of high aspect-ratio single-crystal nanoribbons deposited onto P25, was rationally designed for highly durable, flexible dye-sensitized solar cells. Abstract : Low-temperature processing of dye-sensitized solar cells (DSCs) [B. Oregan, M. Grätzel, Nature, 1991, 353, 737] is crucial to enable their commercialization with low-cost plastic substrates. Much of the previous work in this area has focused on mechanical compression of premade particles on plastic substrates; however, many reported that this technique did not yield sufficient interconnections for high charge carrier transport. Herein, we present bi-layer photoanodes that incorporate microstructured TiO2 sea-urchin-like assemblies, composed of high-aspect-ratio single crystalline nanoribbons, i.e., two-dimensional subunits, which were deposited onto a nanoparticle layer (commercial P25), with a 5.6% conversion efficiency realized. We demonstrate that this Mesoporous Hierarchical Anatase TiO2 (MHAT) nanostructure is beneficial due to its enhanced dye loading as well as enhanced light scattering. Importantly, we also show the benefits of a bi-layer structure where the nanoribbons penetrate into the nanoparticle layer (P25) after cold isostatic pressing (CIP), resulting in improved adhesion between the MHAT top layer and the P25 under layer on the indium tin oxide-coated polyethylene naphthalate (ITO|PEN) substrate, leading to improved mechanical stability and durability, efficient electron transfer pathways, and ultimately, higher solar-to-electric conversion efficiencies.